If p(x) = x2 - 2√2x + 1, then p(2√2) is equal to (A) 0 (B) 1 (C) 4√2 (D) 8√2 + 1

The correct answer is (B) 1

Solution

p(x) = x2 – 2√2x + 1

To obtain p(2√2), let us substitute x = 2√2,

p(2√2) = (2√2)2 – (2√2 × (2√2)) + 1

= (4 × 2) – (4 × 2) + 1

= 8 – 8 + 1

= 1

Was this answer helpful?

 
   

0 (0)

(0)
(0)

Choose An Option That Best Describes Your Problem

Thank you. Your Feedback will Help us Serve you better.

Leave a Comment

Your Mobile number and Email id will not be published. Required fields are marked *

*

*

BOOK

Free Class

Ask
Question